Isolation and Characterisation of Major and Minor Collagens from Hyaline Cartilage of Hoki (Macruronus novaezelandiae) - Cumming, Mathew H. (Mar Drugs, 2019)
The composition and properties of collagen in teleost (bony fish) cartilage have never been studied. In this study, we aimed to identify and characterise all collagen species in the nasal cartilage of hoki (Macruronus novaezelandiae). Four native collagen species were extracted using two techniques, and isolated with differential salt precipitation. We were able to assign the identity of three of these collagen species on the basis of solubility, SDS-PAGE and amino acid analyses. We found that hoki cartilage contains the major collagen, type II, and the minor collagens, type IX and type XI, which are homologous to those found in mammal and chicken cartilage. Using these extraction protocols, we also isolated a full-length type IX collagen from cartilage for the first time. In addition, we detected a 90 kDa, highly glycosylated collagen that has not been identified in any other species. For each isolate, structural and biochemical characterisations were performed using circular dichroism and Fourier transform infrared spectroscopy analyses, and the thermal denaturation properties were determined. Our results showed that the properties of hoki cartilage-derived collagens are similar to those of collagens in mammalian cartilage, indicating that teleost cartilage could provide biological ingredients for the development of biomaterials to treat cartilage-related illnesses.